Clinical Characteristics of the End-of-Life Phase in Children with Life-Limiting Diseases: Retrospective Study from a Single Center for Pediatric Palliative Care - Baumann, Fanni; Hébert, Steven; Rascher, Wolfgang; Wölfle, Joachim; Gravou-Apostolatou, Chara (Children, 2021)
Background: Data on the end-of-life phase of children receiving palliative care are limited. The purpose of this study is to investigate the spectrum of symptoms of terminally ill children, adolescents, and young adults, depending on their underlying disease. Methods: Findings are based on a 4.5-year retrospective study of 89 children who received palliative care before they died, investigating the symptomatology of the last two weeks before death. Results: In this study, the most common clinical symptomatology present in children undergoing end-of-life care includes pain, shortness of breath, anxiety, nausea, and constipation. Out of 89 patients included in this study, 47% suffered from an oncological disease. Oncological patients had a significantly higher symptom burden at the end of life (p < 0.05) compared to other groups, and the intensity of symptoms increased as the underlying disease progressed. The likelihood of experiencing pain and nausea/vomiting was also significantly higher in oncological patients (p = 0.016). Conclusions: We found that the underlying disease is associated with marked differences in the respective leading clinical symptom. Therefore, related to these differences, symptom management has to be adjusted according to the underlying disease, since the underlying disorder seems to exert an influence on the severity of symptoms and thereby on the modality and choice of treatment. This study is intended to aid underlying disease-specific symptom management at the end-of-life care for children, adolescents, and young adults, with a specific focus on end-of-life care in a home environment.
CRIS-Team WoS Importer:2021-07-09

Diagnostic Utility of Interleukin-6 in Early-Onset Sepsis among Term Newborns: Impact of Maternal Risk Factors and CRP Evaluation. - Schleier, Maria; Lubig, Julia; Kehl, Sven; Hébert, Steven; Wölfle, Joachim; van der Donk, Adriana; Bär, Alisa; Reutter, Heiko Martin; Hepp, Tobias; Morhart, Patrick (Children, 2023)
(1) Background: Interleukin-6 (IL-6) levels act as an early infection marker preceding C-reactive protein (CRP) elevation. This study seeks to analyze IL-6 behavior in suspected early-onset sepsis (EOS) cases among term newborns, comparing it to that of CRP and evaluating IL-6's diagnostic utility. We also aim to assess the impact of maternal risk factors on EOS in term newborns, quantifying their influence for informed decision making. (2) Methods: The retrospective data analysis included 533 term newborns who were admitted to our hospital because of suspected EOS. IL-6, CRP, and the impact of maternal risk factors were analyzed in the context of EOS using binomial test, Chi-squared test, logistic and linear regression. (3) Results: In the cases of EOS, both IL-6 and CRP were elevated. The increase in CRP can be predicted by the initial increase in IL-6 levels. Among the assessed risk factors, intrapartum maternal fever (adjusted odds ratio 18.1; 95% CI (1.7-4.1)) was identified as the only risk factor significantly associated with EOS. (4) Conclusions: Employing IL-6 as an early infection marker enhanced EOS diagnostic precision due to its detectable early rise. However, caution is required, as elevations in IL-6 and CRP levels do not exclusively indicate EOS. Increased CRP levels in healthy newborns with maternal risk factors may be attributed to dynamics of vaginal labor.
EVALuna2:549522

Establishment of Specialized Pediatric Palliative Home Care in the Medical Valley of the European Metropolitan Area Nuremberg - Hébert, Steven; Gravou-Apostolatou, Chara; Rascher, Wolfgang (Klinische Pädiatrie, 2017)
Background As part of the 2007 health reform in Germany the structure of outpatient palliative care for children and adolescents was adopted for the first time and then implemented in Erlangen-Nuremberg in 2009. Methods The introduction of Pediatric Palliative Home Care (PPHC) at the Hospital for Children and Adolescents at the University of Erlangen-Nuremberg was retrospectively analyzed between the years 2009 to 2014. Referring medical records (paper-based and electronic) were evaluated systematically. Results Considering 69 patients within this study, 44 (63.8%) died during the investigated period and 61% of these Patients deceased at home. 60 patients (87%) had a written emergency plan, which was jointly developed with patients and particularly their parents and relatives in cooperation with the PPHC team. Over the years and with increasing experience, the number and duration of emergency hospitalization decreased. Even complex therapies, such as patient-controlled analgesia with PCA pump could be implemented on an outpatient basis. Conclusion The descriptive cohort study demonstrates that palliative care for children, despite the medical and structural complexity is possible in an ambulatory setting. It allows a similar, if not better care, compared to inpatient palliative care for children and adolescents, not only for the affected patients, but also for their families.
EVALuna2:34224

"Multisystem Inflammatory Syndrome in Children"-Like Disease after COVID-19 Vaccination (MIS-V) with Potential Significance of Functional Active Autoantibodies Targeting G-Protein-Coupled Receptors (GPCR-fAAb) for Pathophysiology and Therapy. - Schmidt, Marius; Hébert, Steven; Wallukat, Gerd; Ponader, Rolf; Krickau, Tobias; Galiano, Matthias; Reutter, Heiko Martin; Wölfle, Joachim; Agaimy, Abbas; Mardin, Christian; Hörning, André; Hohberger, Bettina (Children, 2023)
BACKGROUND: An infection with SARS-CoV-2 can trigger a systemic disorder by pathological autoimmune processes. A certain type of this dysregulation is known as Multisystemic inflammatory syndrome in children (MIS-C). However, similar symptoms may occur and have been described as Multisystemic inflammatory syndrome after SARS-CoV-2 Vaccination (MIS-V) following vaccination against SARS-CoV-2. We report the case of a 12-year-old boy who was identified with MIS-C symptoms without previous SARS-CoV-2 infection after receiving two doses of the Pfizer-BioNTech COVID-19 vaccine approximately one month prior to the onset of symptoms. He showed polyserositis, severe gastrointestinal symptoms and, consequently, a manifestation of a multiorgan failure. IgG antibodies against spike proteins of SARS-CoV-2 were detected, indicating a successful vaccination, while SARS-CoV-2 Nucleocapsid protein antibodies and SARS-CoV-2 PCR were not detected. Several functional, active autoantibodies against G-protein-coupled receptors (GPCR-fAAb), previously associated with Long COVID disease, were detected in a cardiomyocyte bioassay. Immunosuppression with steroids was initiated. Due to side effects, treatment with steroids and later interleukin 1 receptor antagonists had to be terminated. Instead, immunoadsorption was performed and continued with tacrolimus and mycophenolic acid therapy, leading to improvement and discharge after 79 days. GPCR-fAAb decreased during therapy and remained negative after clinical curing and under continued immunosuppressive therapy with tacrolimus and mycophenolic acid. Follow-up of the patient showed him in good condition after one year. CONCLUSIONS: Infection with SARS-CoV-2 shows a broad and severe variety of symptoms, partly due to autoimmune dysregulation, which, in some instances, can lead to multiorgan failure. Despite its rarity, post-vaccine MIS-C-like disease may develop into a serious condition triggered by autoimmune dysregulation. The evidence of circulating GPCR-fAAb and their disappearance after therapy suggests a link of GPCR-fAAb to the clinical manifestations. Thus, we hypothesize a potential role of GPCR-fAAb in pathophysiology and their potential importance for the therapy of MIS-C or MIS-V. However, this observation needs further investigation to prove a causative correlation.
EVALuna2:547545

“Multisystem Inflammatory Syndrome in Children” (MIS-C) after COVID-19 Infection in the Metropolitan Area of Nuremberg-Erlangen, Germany—Expectations and Results of a Two-Year Period - Hébert, Steven; Schmidt, Marius; Topf, Georg; Rieger, Daniel; Klinge, Jens; Vermehren, Jan; Fusch, Christoph; Grillhösl, Christian; Schroth, Michael; Toni, Irmgard; Reutter, Heiko Martin; Morhart, Patrick; et al. (Children, 2023)
Background: Multisystemic Inflammatory Syndrome in children (MIS-C) is a rare autoimmune disorder occurring after a latency period following acute SARS-CoV-2 infection. The therapeutic regime of MIS-C is adapted to the therapy of the Kawasaki disease, as clinical symptoms are similar. Since the Kawasaki disease can potentially result in severe symptoms, which may even affect long-term health, it is essential to gain further knowledge about MIS-C. Thus, we aimed to investigate the incidence, symptoms, therapeutical procedure and outcome of MIS-C patients in the metropolitan area of Nuremberg-Erlangen during the SARS-CoV2 pandemic. Material and Methods: Retrospective analysis of clinical charts of MIS-C patients was carried out at three children’s hospitals covering the medical care of the metropolitan area of Nuremberg-Erlangen in Germany. Demographic characteristics and symptoms at first visit, their clinical course, therapeutic regime and outcome were recorded within the time period January 2021–December 2022. Results: Analysis of 10 patients (5 male, 5 female) with MIS-C resulting in an incidence of 2.14/100.000 children. The median time between COVID-19 infection and admission to hospital was 5 weeks. The median age was 7 years. Symptoms comprised fever (100%), rash (70%), bilateral non-purulent conjunctivitis (70%) and urticaria (20%). At the time of presentation, diagnosis-defining inflammation parameters were increased and the range for C-reactive protein was 4.13 mg/dL to 28 mg/dL, with a median of 24.7 mg/dL. Procalcitonin was initially determined in six patients (1.92 ng/mL to 21.5 ng/mL) with a median value of 5.5 pg/mL. Two patients displayed leukocytosis and two displayed leukopenia. None of the patients presented coronary pathologies. Nine of the ten patients received intravenous immunoglobulin (IVIG) therapy. In addition, patients received intravenous steroids (80%) and acetylsalicylic acid (80%). Conclusion: SARS-CoV virus may rarely exert multiorgan manifestations due to hyperinflammatory immunological processes. Within two years of the COVID-19 pandemic, we identified ten patients with COVID-induced MIS-C in the metropolitan area Nuremberg-Erlangen. In the description of the patient collective, we can confirm that MIS-C is distinguished from the Kawasaki disease by the lack of coronary manifestations. Interestingly, although having monitored all pediatric facilities in the investigated area, we find lower incidences of MIS-C compared to findings in the literature. In conclusion, an overestimation of incidences in the upcoming MIS-C during the pandemic needs to be considered.
CRIS-Team Scopus Importer:2023-09-08
Keywords: COVID-19; intravenous immunoglobulins; IVIG; mAbs; MIS-C; monoclonal antibodies; Multisystem Inflammatory Syndrome in children

SIADH as a Rare Complication of Foramen Magnum Stenosis in an Infant With Achondroplasia. - Cebeci, Ayse Nurcan; Hébert, Steven; Reutter, Heiko Martin; Rompel, Oliver; Wölfle, Joachim (JCEM Case Reports, 2024)
Achondroplasia is the most common skeletal dysplasia and is associated with serious complications such as foramen magnum stenosis (FMS). This case report describes an infant with achondroplasia who presented with a syndrome of inappropriate antidiuretic hormone secretion (SIADH), secondary to significant FMS and myelocompression. A 2-month-old boy with prenatally diagnosed achondroplasia was referred due to disordered breathing and altered consciousness. On admission, apathy, hypotonus, and hypothermia with typical features of achondroplasia were noticed. Laboratory investigations revealed severe hyponatremia and hypochloridaemia with normal glucose and urea levels. The diagnosis of SIADH was made based on low serum osmolality in the presence of high urine osmolality, along with an elevated copeptin level. An emergency computerized tomography showed a high-grade stenosis at the cranio-cervical junction; subsequent magnetic resonance imaging demonstrated myelocompression. The patient underwent decompression surgery the next day; serum osmolality increased after the operation. Spontaneous breathing after extubation was sufficient whereas tetraplegia persisted despite intensive physiotherapy. Clinicians should be aware of SIADH as a presenting sign of FMS in children with achondroplasia. Further discussion is warranted regarding improving parental education and timing of screening recommendations.
EVALuna2:582017

SIADH as presenting feature of foramen magnum stenosis in a 2-month-old infant with achondroplasia (ACH): case report and discussion on management of infants with ACH in order to reduce the risk of serious complications - Cebeci, Ayse Nurcan; Hébert, Steven; Reutter, Heiko Martin; Wölfle, Joachim (HORMONE RESEARCH IN PAEDIATRICS, 2022)
CRIS-Team WoS Importer:2022-10-07